GAMBARAN PERSEPSI MASYARAKAT TERHADAP PENDERITA HIV/AIDS - Rita Diana Eka Putri; Yulia Irvani Dewi; Nurul " Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aims to describe the public perception to people with HIV/AIDS. This research method is descriptive survey. This study conducted in the community society of Rejosari Village, District of Tenayan Raya, Pekanbaru City. The amount of samples were 93 respondents that appropriate with inclusion criteria and using simple random sampling technique. This research used questionnaire that had been tested for validity and reliability. The analysis was used univariate analysis. The results showed that most of the respondents had a negative perception (68,8%) about people who have HIV/AIDS. The result is expected to the public to change the perceptions about HIV/AIDS, so not to be hated the infected person but hate the disease to make people with HIV/AIDS.can improve their quality of life and can live decently together with other communities. Keywords: community, HIV/AIDS, perception, public